Introduction to political science : Islamic and Western perspectives - Shuriye, Abdi Omar (Ilmiah Publishers Sdn. Bhd., 2000)
Composing an Introduction to Political Science textbook is a rewarding exercise for the subject matter is paramount in both theoretical and practical levels of societal and individual life. The historical development, the origin and current trends of the sciences of politics, not only from the Western aspect but also from the Islamic perspective, are to be introduced. On the one hand, without proper training at the university level producing conscious and visionary intellectuals is almost impossible. On the other hand, without suitable textbooks, the idea of intellecrualism may disappear. Unless the scarcity of Islamized textbooks in the university level, which is obviously becoming a major issue of concern, is attended to, the project of Islamization of knowledge would be impotent. This extended and revised 2nd edition is the most extensive revision. The inclusion of the last two chapters have changed the basic structure of the book. In the course of revising this edition, I owe gratitude to the head of Political Sciences Department, IIIJM, Assoc. Professor Dr. Noore Alam Siddiquee, Professor Dr. Abdul Rashid Moten and Assoc. Prof.Dr. El-Fatih A. AbdulSalam of the aforementioned department.